2021
DOI: 10.5590/jerap.2021.11.1.12
|View full text |Cite
|
Sign up to set email alerts
|

Instructional Supervision and the COVID-19 Pandemic: Perspectives From Principals

Abstract: Six questions that instructional supervisors have been faced with and had to respond to during the COVID-19 crisis include: (a) How do we support teachers in the transition from face-to-face to virtual classes and meetings; (b) How do we focus on addressing the needs of teachers while engaged in remote or online learning; (c) How do we maintain communication, contact, and relationships with teachers; (d) How do we celebrate successes as teachers work with students in the virtual world; (e) How do we assess the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 0 publications
1
17
0
1
Order By: Relevance
“…The main focus of teaching supervision is to build the capacity of teachers to use new teaching and learning models. Collaboration can be established through dialogue between district leaders, schools, and teachers to see their views, concerns, and proposed solutions in the transition to an online learning model (Brock et al, 2021;Hakim, 2021). While Mette (2020) in his study found that teaching leaders play a role towards empowering teachers and students of different backgrounds and needs by providing equal opportunities for all students to gain knowledge and guidance.…”
Section: To Identify the Role That Instructional Leaders Need To Play...mentioning
confidence: 99%
See 4 more Smart Citations
“…The main focus of teaching supervision is to build the capacity of teachers to use new teaching and learning models. Collaboration can be established through dialogue between district leaders, schools, and teachers to see their views, concerns, and proposed solutions in the transition to an online learning model (Brock et al, 2021;Hakim, 2021). While Mette (2020) in his study found that teaching leaders play a role towards empowering teachers and students of different backgrounds and needs by providing equal opportunities for all students to gain knowledge and guidance.…”
Section: To Identify the Role That Instructional Leaders Need To Play...mentioning
confidence: 99%
“…All teacher complete modules that cover a learning management system (LMS), instructional design for online learning, and video conferencing tools. A resource website has also been created to provide staff with additional support, and teaching leaders meet with teachers individually as needed (Brock et al, 2021).…”
Section: To Identify the Role That Instructional Leaders Need To Play...mentioning
confidence: 99%
See 3 more Smart Citations